Interleukin-6 trans-signaling is a candidate mechanism to drive progression of human DCCs during clinical latency - Werner-Klein, Melanie; Grujovic, Ana; Irlbeck, Christoph; Obradović, Milan; Hoffmann, Martin; Koerkel-Qu, Huiqin; Lu, Xin; Treitschke, Steffi; Köstler, Cäcilia; Botteron, Catherine; Weidele, Kathrin; Werno, Christian; et al. (Nature Communications, 2020)
Although thousands of breast cancer cells disseminate and home to bone marrow until primary surgery, usually less than a handful will succeed in establishing manifest metastases months to years later. To identify signals that support survival or outgrowth in patients, we profile rare bone marrow-derived disseminated cancer cells (DCCs) long before manifestation of metastasis and identify IL6/PI3K-signaling as candidate pathway for DCC activation. Surprisingly, and similar to mammary epithelial cells, DCCs lack membranous IL6 receptor expression and mechanistic dissection reveals IL6 trans-signaling to regulate a stem-like state of mammary epithelial cells via gp130. Responsiveness to IL6 trans-signals is found to be niche-dependent as bone marrow stromal and endosteal cells down-regulate gp130 in premalignant mammary epithelial cells as opposed to vascular niche cells. PIK3CA activation renders cells independent from IL6 trans-signaling. Consistent with a bottleneck function of microenvironmental DCC control, we find PIK3CA mutations highly associated with late-stage metastatic cells while being extremely rare in early DCCs. Our data suggest that the initial steps of metastasis formation are often not cancer cell-autonomous, but also depend on microenvironmental signals.
CRIS-Team Scopus Importer:2020-10-16